A conserved motif in the immune-subdominant RAP-1 related antigen of Babesia bovis contains a B-cell epitope recognized by antibodies from protected cattle - Rojas, Manuel J.; Bastos, Reginaldo G.; Navas, Jinna; Laughery, Jacob M.; Lacy, Paul A.; Suarez, Carlos E. (Frontiers in Immunology, 2024)
Introduction Babesia bovis, a tick-borne apicomplexan parasite causing bovine babesiosis, remains a significant threat worldwide, and improved and practical vaccines are needed. Previous studies defined the members of the rhoptry associated protein-1 (RAP-1), and the neutralization-sensitive rhoptry associated protein-1 related antigen (RRA) superfamily in B. bovis, as strong candidates for the development of subunit vaccines. Both RAP-1 and RRA share conservation of a group of 4 cysteines and amino acids motifs at the amino terminal end (NT) of these proteins. Methods and results Sequence comparisons among the RRA sequences of several B. bovis strains and other Babesia spp parasites indicate a high level of conservation of a 15-amino acid (15-mer) motif located at the NT of the protein. BlastP searches indicate that the 15-mer motif is also present in adenylate cyclase, dynein, and other ATP binding proteins. AlphaFold2 structure predictions suggest partial exposure of the 15-mer on the surface of RRA of three distinct Babesia species. Antibodies in protected cattle recognize a synthetic peptide representing the 15-mer motif sequence in iELISA, and rabbit antibodies against the 15-mer react with the surface of free merozoites in immunofluorescence. Discussion and conclusion The presence of the 15-mer-like regions in dynein and ATP-binding proteins provides a rationale for investigating possible functional roles for RRA. The demonstrated presence of a surface exposed B-cell epitope in the 15-mer motif of the B. bovis RRA, which is recognized by sera from protected bovines, supports its inclusion in future subunit epitope-based vaccines against B. bovis.